2021
DOI: 10.1371/journal.pone.0255592
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate goals predict COVID-19 health behaviors during the SARS-CoV-2 pandemic

Abstract: We predicted that people with compassionate goals to support others and not harm them practiced more COVID-19 health behaviors during the SARS-CoV-2 pandemic to protect both themselves and others from infection. Three studies (N = 1,143 American adults) supported these predictions and ruled out several alternative explanations. Compassionate goals unrelated to the health context predicted COVID-19 health behaviors better than the general motivation to be healthy (Studies 2 and 3). In contrast, general health m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…In the COVID-19 pandemic, adherence to preventive behaviors was shown to be more likely among individuals with high empathy and care for others and less likely among those with egoistic motives (Christner et al, 2020;Huang et al, 2020;Ospina et al, 2021). We therefore found it important to cover individualist versus collectivist motives in some of our studies.…”
Section: Individualism-collectivismmentioning
confidence: 86%
“…In the COVID-19 pandemic, adherence to preventive behaviors was shown to be more likely among individuals with high empathy and care for others and less likely among those with egoistic motives (Christner et al, 2020;Huang et al, 2020;Ospina et al, 2021). We therefore found it important to cover individualist versus collectivist motives in some of our studies.…”
Section: Individualism-collectivismmentioning
confidence: 86%
“…People with more compassionate goals reported doing COVID-19 health behaviors because they wanted to protect themselves, close others, and distant others from COVID-19. (Ospina et al, 2021) Prosocial motivation…”
Section: Covid-19 Health Behaviorsmentioning
confidence: 99%
“…The concern-for-self and concern-for-others motivation not only impact individual information processing tendencies but also individual actual behaviors (Abu-Tayeh et al, 2018;Campos-Mercade et al, 2021;Jordan et al, 2021;Oreg & Nov, 2008;Ospina et al, 2021). Regarding behaviors of contributors in open-source projects, Oreg and Nov (2008) found that individuals who contribute to software development place more emphasis on self-concern motivation such as reputation building and self-development, while content contributors concern with helping others more.…”
Section: The Effect Of Concern-for-self and Concern-for-others Motiva...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both pro-sociality and trust can enable individuals to cope up with difficult situations caused by pandemic, extend help towards others and cooperate with each other for repairing the damage caused to the societal setup, political institutions and the economic development (Bjørnskov and Méon 2013 ; Brañas-Garza et al 2022 ; Brück et al 2020 ). Moreover, recent evidence also suggests that prosocial people are more likely to take preventive measures (such as social distancing, staying home, wearing masks and intent of vaccination) for the containment of Covid-19 and hence make individual-level contributions for the overall safety and improvement of the society (Campos-Mercade et al 2021 ; Ospina et al 2021 ; Yu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%